2019
DOI: 10.1037/com0000148
|View full text |Cite
|
Sign up to set email alerts
|

Preference for attractive faces is species-specific.

Abstract: Studies on facial attractiveness in human adults, infants, and newborns have consistently reported a visual preference for faces rated as attractive compared with faces rated as unattractive. Biological accounts of facial attractiveness have typically presented such preferences as arising from adaptations for mate choice or as by-products of general sensory bias. In this cross-species study, we examined whether explicit ratings of attractiveness made by human judges would predict implicit visual preferences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…These findings indicated that monkeys prefer visual stimuli that humans find aesthetically pleasing, as visual symmetry is perceived as attractive in a variety of domains (Little, 2014). Furthermore, when it comes to faces, ratings of rhesus macaque face attractiveness by human judges can predict implicit visual preferences in rhesus macaques (Damon et al, 2019).…”
Section: How Do Other Species Process Faces?mentioning
confidence: 86%
“…These findings indicated that monkeys prefer visual stimuli that humans find aesthetically pleasing, as visual symmetry is perceived as attractive in a variety of domains (Little, 2014). Furthermore, when it comes to faces, ratings of rhesus macaque face attractiveness by human judges can predict implicit visual preferences in rhesus macaques (Damon et al, 2019).…”
Section: How Do Other Species Process Faces?mentioning
confidence: 86%
“…It is considered that visual preference is modulated by two mutually not exclusive factors, interest (determined by the information about the stimulus) and pleasure (determined by the attractiveness of the stimulus) (Damon et al, 2019;Humphrey, 1972). In the case of chimpanzees, it is possible that while infant stimuli capture their visual attention more effectively (as measured by the looking time), they may not necessarily perceive these stimuli as more rewarding (as measured by the spontaneous motivation to watch) compared to adult stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual bias views would generally assume that the type of stimuli should not matter for symmetry preferences. Studies [36,[38][39][40][41] show, however, that stimuli type makes a difference. For example, symmetry is preferred more in human faces than in abstract face-like stimuli [36] and more in human faces than in either monkey faces or abstract art images [39].…”
Section: Introductionmentioning
confidence: 98%
“…Asking humans to rate non-human primate faces from three different primate groups for attractiveness has shown that some cues used by humans to judge attractiveness in humans also apply to non-human primates, but only in Catarrhines, the primate group most similar to humans [40]. Comparing human and macaque monkey visual preferences, it has been shown that humans show visual preferences for human faces rated as attractive by humans while macaques show visual preferences for macaque faces rated as attractive by humans [41]. Such preferences appear mediated partly by species as humans did not show visual preferences for attractive macaque faces and macaques did not show visual preferences for attractive human faces [41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation